Darmok and Jalad at the Psych Ward: A Case Demonstration of How to Creatively Communicate with a 19-Year-Old Patient with Autism Spectrum Disorder. (24th February 2021) - Kim, Elizabeth; Martin, Katherine; Karper, Laurence; Maru, Siddhartha; Driscoll, Maggie
Abstract : Difficulties in communication often arise between individuals with autism spectrum disorder and their treating physicians because both sides struggle to find a common ground. The story of Darmok and Jalad at Tanagra from Star Trek: The Next Generation nicely exemplifies how two populations that spoke different languages were still able to find a creative way to communicate with each other. This story is used as a metaphor to illustrate how a novel connection was made with a 19-year-old patient with autism spectrum disorder who was admitted to the inpatient psychiatric unit.